Fluorescence-enabled evaluation of nasal tract deposition and coverage of pharmaceutical formulations in a silicone nasal cast using an innovative spray device - Davide D'Angelo; Stefan Kooij; Frank Verhoeven; Fabio Sonvico; Cees van Rijn (Journal of Advanced Research, 2023)
Introduction: The characterisation of nasal formulations is a critical point. However, there are still no recommendations or guidelines in terms of standard approaches for evaluating the formulation's nasal deposition and/or coverage profile. This study optimises a method for quantifying silicone nasal cast deposition and coverage of liquid formulations using different nasal devices. Objectives: The present work investigates the nasal deposition and coverage patterns of innovative nasal spray nozzles producing slow velocity soft mists, using a nasal cavity replica and a fluorescent dye. Methods: The study of the deposition pattern of a fluorescent liquid formulation in a transparent nasal cast was carried out in both the presence and absence of a simulated inhalation flow. The extent of the deposition pattern was investigated using ImageJ and fluorescence in the nasal cast, quantified by fluorometric analysis. The particle size distribution and initial droplet velocity were determined using a laser diffractometer and a high-speed camera with a frame rate of 1000 fps. Results: A uniform intranasal coverage was obtained with droplets of a volume median particle size (Dv50) between 15 and 25 µm in airflow between 10 and 30 L/min. In these conditions, aerosol formulations can be uniformly deposited in the vestibule and turbinate cavity nasal regions, with less than 10 % passing beyond the nasopharyngeal region. Conclusion: The method applied allowed for the determination of the coverage of the nasal cast in different regions using images analysis and fluorometric analysis. Droplet velocity is a critical parameter in the deposition in the nasal cavity. With standard swirl nozzles, many droplets are found on the surface of the nasal vestibule. Soft mist nozzles produce smaller droplets at a much lower initial velocity (<1 m/s), resulting in a more uniform coverage.